Impact Of Palm Oil Plantation Development on Urbanization - Nasution, Zulkarnain; Wahyuni, Sri (Social Sciences Insights Journal, 2024)
The province of North Sumatra is one of the regions in Indonesia that has experienced rapid growth in the oil palm plantation sector. Over the past decade, the area of oil palm plantations in North Sumatra has continued to increase, followed by an increase in palm oil production and exports. However, the growth of this plantation sector has also had a significant impact on the pattern of urbanization in the province. This study aims to analyze how the development of oil palm plantations has influenced the urbanization process in the Province of North Sumatra. The research method used is a combination of secondary data analysis from various sources, as well as in-depth interviews with relevant stakeholders. The results of the study show that the development of oil palm plantations has attracted migrant workers from rural areas to urban areas in North Sumatra. This has resulted in an increase in the urban population, the growth of slums, and increased demands for the provision of infrastructure and public services in major cities. On the other hand, plantation development has also created new economic growth centers in rural areas, thus encouraging spatial urbanization. The findings of this study indicate the need for synchronization between plantation development policies and integrated spatial planning to comprehensively manage the impact of urbanization in the Province of North Sumatra. This effort is expected to promote more equitable and sustainable economic growth in the region.